Time-Specific Effects of Ethanol Exposure on Cranial Nerve Nuclei: Gastrulation and Neuronogenesis - Mooney, Sandra M. (2007)
During the development of the central nervous system, neurons pass through critical periods or periods of vulnerability. We explored periods of vulnerability for cranial nerve nuclei by determining the effects of acute exposure to ethanol during development on the number of neurons in mature brainstem. Long-Evans rats were injected with 2.9 g ethanol/kg body weight on one day between gestational day (G) 7 and G13, inclusive. Two hours later, animals received a second injection of 1.45 g/kg. Controls were injected with equivalent volumes of saline. Brainstems of 31-day-old offspring were cryosectioned and stained with cresyl violet. Stereological methods were used to determine the volume and numerical density of neurons in three trigeminal sensory nuclei (the principal sensory nucleus of the trigeminal nerve, and the oral and interpolar subnuclei of the spinal trigeminal nuclear complex) and three motor nuclei (the trigeminal, facial, and hypoglossal nuclei). The numbers of neurons in most nuclei were lower following early (on G7 and/or G8) or later (on G12 and/or G13) exposure. Only the trigeminal interpolar nucleus was affected by neither early nor late ethanol exposure. Thus, prenatal exposure to ethanol affects the number of neurons in brainstem nuclei in a time-dependent manner. Windows of vulnerability coincide with gastrulation (G7/G8) and the period of neuronal generation (G12/G13).